Psi Lords (2019) #3 - Lente, Fred Van (Valiant Entertainment, 2022)
The cosmic Quartet begins to master their jaw-dropping powers and unlock deeper meanings to their newfound abilities! Dangerous aliens have targeted the Quartet, and they'll stop at nothing until they've eliminated the team. Plus, the lost history of the Psi-Lords revealed?!